ILLOCUTIONARY ACTS IN THE MAIN CHARACTERS’ UTTERANCES IN “SPIDER-MAN: NO WAY HOME” MOVIE - Risman, Noviyanti; Weda, Sukardi (Journal of English Literature and Linguistic Studies, 2024)
This study concerns the types of illocutionary acts contained in the main character’s utterances in Spider-Man: No Way Home Movie. As well as the context that builds the illocutionary act. The writer aims to examine the illocutionary acts in the utterances uttered by Peter Parker aka Spider-Man, the main character in this movie. The writer uses a pragmatic approach to discussing illocutionary acts and the context that builds them on the main character’s utterances. The data in this study are the main character’s utterances contained in the film script. The data collection procedure was to watch the movie carefully, read the movie script, then select and classify the data obtained based on the type of illocutionary act. The writer uses the theory of illocutionary acts from John Searle (1979). Then determine the elements that build the illocutionary act using the theory from Dell Hymes (1975). The results of the study found 4 types of illocutionary acts contained in the utterances of Peter Parker aka Spider-Man, the main character in the Spider-Man: No Way Home movie. These types are directive, representative, expressive, and commissive. The researcher also identified the elements that build the illocutionary act, namely setting and scene, participants, ends, act sequences, keys, instrumentalities, norms of interactions, and genre.